Konstruksi Makna Dimensi Nilai Ilahiyah Dan Nilai Insaniyah Dalam Film “Atas Nama Surga”: Analisis Semiotika - Putri Bunga Yossilia; Fafi Inayatillah (CV. SINAR HOWUHOWU, 2026)
In the modern era, film has become a communication medium that is not only a means of entertainment, but also a space for constructing meaning that represents values ​​in life, including religious values. Research on religious values ​​in films generally still focuses on introducing religious messages without examining how these values ​​are constructed through a complete sign system. Therefore, this study aims to describe the representation of the dimensions of divine and human values ​​contained in the film